Small molecules targeting the NEDD8·NAE protein–protein interaction. Issue 4 (14th December 2020) - Lin, Chen-Ming; Jiang, Zhengyang; Gao, Zhe; Arancillo, Maritess; Burgess, Kevin
Abstract : Discovery of the first NEDDylation inhibitor, that targets the NEDD8·NAE protein–protein interaction, was acheived using the Exploring Key Orientations (EKO) approach. Abstract : Ubiquitination is a major controller of protein homeostasis in cells. Some ubiquitination pathways are modulated by a NEDDylation cascade, that also features E1 – 3 enzymes. The E1 enzyme in the NEDDylation cascade involves a protein–protein interaction (PPI) between NEDD8 (similar to ubiquitin) and NAE (NEDD8 Activating Enzyme). A small molecule inhibitor of the ATP binding site in NAE is in clinical trials. We hypothesized a similar effect could be induced by disrupting the NEDD8·NAE PPI, though, to the best of our knowledge, no small molecules have been reported to disrupt this to date. In the research described here, Exploring Key Orientations (EKO) was used to evaluate several chemotype designs for their potential to disrupt NEDD8·NAE; specifically, for their biases towards orientation of side-chains in similar ways to protein segments at the interface. One chemotype design was selected, and a targeted library of 24 compounds was made around this theme via solid phase synthesis. An entry level hit for disrupting NEDD8·NAE was identified from this library on the basis of its ability to bind NAE ( K i of 6.4 ± 0.3 μM from fluorescence polarization), inhibit NEDDylation, suppress formation of the corresponding E1 – 3 complexes as monitored by cell-based immunoblotting, and cytotoxicity to K562 leukemia cells via early stage apoptosis. The cell-based immunoblot assay also showed the compound caused NEDD8 to accumulate in cells, presumably due to inhibition of the downstream pathways involving the E1 enzyme. The affinity and cellular activities of the hit compound are modest, but is interesting as first in class for this mode of inhibition of NEDDylation, and as another illustration of the way EKO can be used to evaluate user-defined chemotypes as potential inhibitors of PPIs.